The Judicial Review of the Responsibilities of the Company to the Payment of the Money Guarantee the Death of Labor based on Law Number 24 the Year 2011 about BPJS Employment - Triono Edy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The implementation of Act No. 24 2011 is a rule that should be reviewed because many pro-cons who must be responsible for work accidents employees. Here, the author is interested in examining about the judicial review of Corporate Responsibility for the payment of the money guarantee the death of Labor Based on Act No. 24 The year 2011 About BPJS. And here is the author took three formulations of the problem is how the general settings employment social security program in Indonesia, how the role of the law in the BPJS provides protection against the sacrifice guarantee the death of work accidents in Indonesia and law sanctions for companies who are unaware of the responsibility of safety against workers based on Act No. 24 The year 2011 About BPJS. The type of this bachelor theses researches using qualitative research, with wearing the kind of legal research normative and data collection technique use the secondary technique, which consists of the Primary legal materials, secondary, and tertiary preventive measures and data collection method used is a library research method (Library Research).